PENERAPAN TEKNIK PENYUSUNAN MENI DI RESTORAN BENGAWAN SOLO HOTEL SAHID JAYA, JAKARTA [The Aplication of Menu Engineering at Bengawan Solo Restaurant, Sahid Jaya Hotel Jakarta] - Musa Hubies; Sindi Astu Banuhapsari (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2001)
Menu engineering (ME) is a step-by-step process wich is designed to help management in evaluating the current and future menu pricing, menu composition and to set decisions about price and menu. The main objectives of ME are tomake the next menu more profitable and to attract of guest’s attention. It has two critical aspect, that are contribution margin/CM (related to profit) and menu mix/MM (related to an item popularity rate amoing other item). The combination of CM and MM wll result in an item classification (star, plowhorse, question and dog), so that management can design the decision alternatives related to menu item.From the ME application for four months, Bengawan Solo Restaurant has 10 star item menu, 13 qustion items, 2 plowhorse items and 9 dog items. In this case, selling technique performed by waiters and waitresses also influence the ME result. The menegement concerns about the physical presentation and kitchen location. The quality handling should not only be conducted physically, but also pay more attention to halal aspect and food safety or HACCP (hazard analysis and certical control point), in order to produce high quality product that are safe to be consumed.